FRAUD DETECTION OF FINANCIAL STATEMENTS WITH PENTAGON FRAUD ANALYSIS - Afifah Fadhilah; Deliana Deliana; Abdul Rahman; Selfi Afriani (Kajian Akuntansi, 2025)
Abstract.This study aims to determine the effect of financial stability, financial targets, external pressure, external auditor quality, ineffective monitoring, change of auditor, total accruals, CEO education, CEO founder, CEO duality, and political connections on financial statements fraud in Consumer Cyclicals companies listed on the Indonesian Stock Exchange (IDX) over the observation period of 2020-2024. This research is structured based on the Fraud Pentagon theory, which integrates five elements: Pressure, Opportunity, Rationalization, Compentence, and Arrogance, by testing variables related to these elements. The sampling method used purposive sampling, resulting in 78 companies meeting the criteria from 166 companies. Logistic regression analysis was used with SPSS version 29 software. The results showed that external pressure significantly influenced financial statement fraud, while financial stability, financial target, external auditor quality, ineffective monitoring, change of auditor, total accruals, CEO education, CEO founder, CEO duality, and political connections did not significantly influence financial statement fraud. The overall conclusion of this stud is that among the various elements of the Fraud Pentagon tested, only the Pressure element, specifically measured by External Pressure, proves to be a significant driving factor for financial statement fraud in the Consumer Cyclicals sector on the IDX.